2018
DOI: 10.3390/ijms19030820
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the In Vivo Anti-Inflammatory Actions of Simvastatin-Loaded Porous Microspheres on Inflamed Tenocytes in a Collagenase-Induced Animal Model of Achilles Tendinitis

Abstract: Tendon rupture induces an inflammatory response characterized by release of pro-inflammatory cytokines and impaired tendon performance. This study sought to investigate the therapeutic effects of simvastatin-loaded porous microspheres (SIM/PMSs) on inflamed tenocytes in vitro and collagenase-induced Achilles tendinitis in vivo. The treatment of SIM/PMSs in lipopolysaccharide (LPS)-treated tenocytes reduced the mRNA expressions of pro-inflammatory cytokines (Matrix metalloproteinase-3 (MMP-3), cyclooxygenase-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 45 publications
2
21
0
1
Order By: Relevance
“…In the present study, tenocytes were treated with IL-1β in order to mimic the inflamed condition in vitro. Our previous studies reported that LPS-stimulated tenocytes increase gene expression levels for cytokines (i.e., ADAMTS-5, COX-2, IL-6, TNF-α) as well as ECM-degrading proteinases (i.e., MMP-3 and MMP-13) [1,3]. We found that DEX/PMS systems markedly suppressed the mRNA levels of these cytokines in IL-1β-stimulated tenocytes.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…In the present study, tenocytes were treated with IL-1β in order to mimic the inflamed condition in vitro. Our previous studies reported that LPS-stimulated tenocytes increase gene expression levels for cytokines (i.e., ADAMTS-5, COX-2, IL-6, TNF-α) as well as ECM-degrading proteinases (i.e., MMP-3 and MMP-13) [1,3]. We found that DEX/PMS systems markedly suppressed the mRNA levels of these cytokines in IL-1β-stimulated tenocytes.…”
Section: Discussionmentioning
confidence: 52%
“…To produce DEX/PMSs, a simple fluidic device equipped was used as previously described [1,3,13]. First, 140 mg of poly (lactic-co-glycolic acid) (PLGA, 50 : 50, Mw: 30,000-60,000 g/mol, Sigma-Aldrich, St. Louis, MO, USA) was clearly solubilized in dichloromethane (DCM, 7 mL).…”
Section: Fabrication Of Dex-contained Pmss (Dex/pmss)mentioning
confidence: 99%
See 2 more Smart Citations
“…The content of SIM in the microspheres was determined using an ultraviolet (UV) spectrophotometer (Beckman Coulter, Inc., Brea, CA, USA) (26,2830). UV scanning from 100 to 1,000 nm was used to identify the absorption peak of SIM.…”
Section: Methodsmentioning
confidence: 99%